Understanding and Scope of Management of Educational Facilities and Infrastructure - Astuti, Mardiah; Suryana, Icha; Yuke, Dea Patricia; Aji Dara, Della Sevta; Masitho, Masitho; Hartanti, Agda; Pratiwi, Adelia (Jurnal Sustainable, 2023)
Managing the buildings and equipment that schools employ to provide high-quality education is known as educational facility and infrastructure management. Planning, acquiring, inventorying, distributing, using, maintaining, eliminating, and accounting for educational infrastructure and facilities are all part of this process. Managing educational facilities and infrastructure should aim to do the following: satisfy demands, boost performance, increase service life, decrease repair costs, and calculate the effective cost of maintenance. The essay delves into the definition, purpose, scope, and management method of educational facilities and infrastructure by drawing from a number of pertinent literary sources. Planning, purchasing, regulating, using, and eliminating are the five recognised primary aspects of educational infrastructure and facility management. Because of their interdependence, these five scopes are essential for efficient infrastructure management.